PENINGKATAN KEMAMPUAN MENYIMPULKAN ISI BERITA YANG DIBACAKAN MELALUI METODE DISKUSI DALAM PEMBELAJARAN DARING - Muhakim, Arief (Universitas Wijaya Kusuma Surabaya, 2021)
This study aims to improve the ability to conclude the content of the news read through the technique of applying the online discussion method (in the network). The research method uses classroom action research (PTK). The research was carried out in the odd semester of the 2020/2021 school year for two cycles in October 2020 at Salman Al Farisi Junior High School, Bandung. Based on the findings and results of data analysis, it can be concluded that learning through the discussion method can improve students' ability to conclude news content. This is based on the following findings. Through the discussion method, students are more enthusiastic and enthusiastic in concluding the content of the news that is read. This can be observed based on the results of reflection activities in cycle I, from 25 students as many as 17 students stated that they were more enthusiastic about concluding news content using the discussion method, while in cycle II all students stated that they were more enthusiastic about concluding the content of the news using the discussion method.Â